Level structure of 73 Se from the 72 Ge (α,3ny) reaction. - Behar, M.; Filevich, Alberto; García Bermúdez, G.; Hernandez, A. M.; Mariscotti, M. A. J. (North Holland Publishing, 1976)
Fil: Behar, M. Comisión Nacional de Energía Atómica; Argentina